Software Processing Features of Photoplethysmography Signals - Dzundza, B.S.; Dombrovskyi, S.V.; Shtun, M.V.; Chinchoy, O.O.; Morgun, A.V. (Physics and Chemistry of Solid State, 2025)
The study explores the potential of using photoplethysmography to analyze human health. This method is considered a promising non-invasive technique for monitoring biomedical indicators such as heart rate, respiratory rate, cardiovascular system condition, and blood oxygen saturation. The study analyzes methods for processing photoplethysmography signals and develops an algorithm for signal analysis. This algorithm compensates for respiratory signal modulation, quickly identifies key extremum points, and determines heart rate, respiratory rate, cardiovascular system indicators, and blood oxygen saturation. The application of this algorithm places minimal load on the microcontroller, enabling the development of a low-power human health monitoring system.